O agronegócio e as intoxicações agudas por agrotóxicos em Mato Grosso, Brasil - Silva, Shinarley Azevedo da (2014)
The pesticide poisoning are characterized as public health problem worldwide and cause irreversible damage to the body of man, can evolve to death. They result in the production chain generated by agribusiness and impact on the environment and on human and animal lives. Objective: To evaluate reports of pesticide poisoning and its relation to the use of these products in Mato Grosso, in the period 2007 to 2012 Methods: Study conducted in two stages: first descriptive analysis was performed on notifications of pesticide poisoning recorded in SINAN, covering sixteen health regions of Mato Grosso, in the period from 2007 to 2012 and its relation to the use of this product in the state. In the second step was carried out analytical study on these pesticide poisoning and performed descriptive, bivariate and multiple regression analyzes. Results: Step 1 Of 760 complaints analyzed, the regional who had the highest percentages of cases are inserted in the agribusiness chain in this state: Sinop (16%), Rondonópolis (13%), Barra do Garças (11%) and Tangará da Serra (9%). Most cases occurred from accidental way (39%) followed by attempted suicide (29%). Step 2: Of the 312 notifications resulting from step 1, the highest incidences of poisoning occurred in males (69.23%). The age group with the highest frequency was 20-39 years. 46.51% were mixed race, and more than half the cases (70%) had completed elementary level up. The venue of the exhibition was the work environment (48%), accidental poisoning (38%). In the months from October to March the major events that coincide with the period of harvest were verified. In 66% of cases there was in hospital and 2% of cure was intoxicated with sequelae. Associations were found between three variables on the characteristics of pesticide exposure and the outcome variable "if they are from work", which are: the working environment, pesticide use in agriculture and environmental exposure, and all with p <0.001. Considerations: The results point to the negative impacts of the agribusiness production process, indicating that the pesticides that are used intensively in agricultural production, are inducing acute poisoning which coincide with the period of the harvest, with the highest incidences are higher in regional production . The data suggest specific to be included in training for professionals of health issues: a) classification of toxic agent; b) trade name of the pesticide; c) Active Ingredient and other details of the surveillance research of exogenous intoxications SINAN. A study on the feasibility of integrating the Pesticide Information System (CIS) database SINAN as a means of minimizing errors in the completion of the variables related to pesticides is recommended. It is necessary to implement the actions of the health surveillance of populations exposed to pesticides in Mato Grosso.